Bioactive substance contents and therapeutic potential for skin inflammation of an herbal gel containing Derris reticulata and Glycyrrhiza glabra - Warissara Sangkaew; Wipawadee Sianglum; Suttiwan Wunnoo; Supayang Piyawan Voravuthikunchai; Nantiya Joycharat (Taylor & Francis Group, 2024)
Context Derris reticulata Craib. and Glycyrrhiza glabra L., of the Fabaceae, have been used as active components in Thai herbal formulas for the treatment of fever and skin diseases.Objective To evaluate the physicochemical and pharmacological properties of the developed herbal gel formulation containing the combined extract from D. reticulata stem wood and G. glabra root (RGF).Materials and methods The potential of the herbal gel formulation containing RGF (8% w/w) as the active ingredient was studied by evaluating the anti-inflammatory, antioxidant, and anti-Staphylococcus aureus activities using quantitative reverse transcription-polymerase chain reaction assay, spectrophotometric method, and broth microdilution technique, respectively. The reference standards for the biological testing included Nω-nitro-L-arginine (L-NA), ascorbic acid, catechin, and penicillin G. The stability study of the RGF herbal gel was performed by a heating-cooling test (at 45 °C for 24 h and at 4 °C for 24 h/1 cycle; for 6 cycles), and the bioactive marker compounds in the herbal gel were investigated by the HPLC technique.Results RGF showed promising pharmacological effects, particularly on its anti-inflammatory property (IC50 73.86 µg/mL), compared to L-NA (IC50 47.10 µg/mL). The RGF-containing gel demonstrated anti-inflammatory (IC50 3.59 mg/mL) and free radical scavenging effects (IC50 0.05-4.39 mg/mL), whereas it had no anti-S. aureus activity (MIC > 10 mg/mL). The active ingredient in the developed herbal gel significantly inhibited lipopolysaccharide-induced nitric oxide production by downregulating iNOS mRNA levels. The contents of the bioactive markers in the RGF gel (lupinifolin and glabridin) did not change significantly after stability testing.Discussion and conclusions The RGF-containing gel has potential to be further developed as an herbal product for the treatment of skin inflammation.